Transforming Growth Factor-β1/Smad7 in Intestinal Immunity, Inflammation, and Cancer - Troncone, Edoardo; Marafini, Irene; Stolfi, Carmine; Monteleone, Giovanni (Frontiers in Immunology, 2018)
In physiological conditions, the activity of the intestinal immune system is tightly regulated to prevent tissue-damaging reactions directed against components of the luminal flora. Various factors contribute to maintain immune homeostasis and diminished production and/or function of such molecules trigger and/or propagate detrimental signals, which can eventually lead to chronic colitis and colon cancer. One such a molecule is transforming growth factor-1 (TGF-1), a cytokine produced by many inflammatory and non-inflammatory cells and targeting virtually all the intestinal mucosal cell types, with the down-stream effect of activating intracellular Smad2/3 proteins and suppressing immune reactions. In patients with inflammatory bowel diseases (IBD), there is defective TGF-1/Smad signaling due to high Smad7, an inhibitor of TGF-1 activity. Indeed, knockdown of Smad7 with a specific antisense oligonucleotide restores endogenous TGF-1 activity thereby inhibiting inflammatory pathways in patients with IBD and colitic mice. Consistently, mice over-expressing Smad7 in T cells develop severe intestinal inflammation in various experimental models. Smad7 expression is also up-regulated in colon cancer cells, in which such a protein controls positively intracellular pathways that sustain neoplastic cell growth and survival. We here review the role of TGF-β1 and Smad7 in intestinal immunity, inflammation and cancer.